Trends in seroprevalence of influenza A virus infections in pigs in France (2008–2022) - Séverine Hervé; Nicolas Rose; Nicolas Barbier; Stéphane Quéguiner; Stéphane Gorin; Roselyne Fonseca; Gaëtan Pinsard; Gautier Richard; Agnès Jardin; Gaëlle Simon (Porcine Health Management)
Abstract Background Swine influenza A viruses (swIAV) are highly contagious zoonotic pathogens that cause an acute respiratory infection in pigs, presenting substantial economic and health risks for animals and farmers. This drives the pig industry and stakeholders in animal health to monitor swIAV in livestock. In the 10 years prior to the 2009 flu pandemic, H1avN1 (HA-1C.2.1) and H1huN2 (HA-1B.1.2.3) circulated in pig herds in France while H3N2 was not detected. The H1N1pdm (HA-1A.3.3.2) lineage became enzootic after its introduction. In 2020, a new H1avN2 genotype (HA-1C.2.4) emerged, altering the frequencies of enzootic swIAV lineages. To support our knowledge built on event-based surveillance and gain information on swIAV infections, serological studies were conducted. Three independent surveys were performed nationally in 2008 and in 2018 (before and after the A/H1N1pdm09 pandemic, respectively), and in North West in 2022 (after the H1avN2 emergence in Brittany area). These surveys aimed to estimate swIAV prevalence in livestock using ELISA on fattening pigs and hemagglutination inhibition (HI) tests to determine the relative frequencies of different swIAV lineages. Results The national seroprevalence estimated by ELISA was 91% [83–96]CI95 in 2008, and 87% [81–92]CI95 in 2018. In 2022, seroprevalence in the North West reached 91% [73–97]CI95. In each survey, antibodies against several swIAV subtypes were detected simultaneously by HI tests in approximately 25% of ELISA-positives batches. In 2008, anti-HA-1C.2.1 antibodies were widespread, while anti-HA-1B.1.2.3 antibodies were found in most regions except for the South West. In contrast, H3N2 seroprevalence was very low, restricted to the North East. By 2018, anti-HA-1C.2.1 antibodies remained the most prevalent and anti-H3 antibodies the weakest, but anti-HA-1B.1.2.3 prevalence had strongly decreased, while anti-HA-1A.3.3.2 antibodies were detected nationwide. In 2022, the North West showed the highest seroprevalence for H1avN1 (HA-1C.2.1), followed by H1avN2 (HA-1C.2.4), H1N1pdm and finally H1huN2. Conclusions These surveys revealed a high and sustained swIAV seroprevalence, particularly in areas with a high density of pigs. They also highlighted changes in the relative frequencies of anti-HA antibodies, reflecting viral emergence and dynamics. Despite challenges in interpreting HI test results, the surveys provided valuable data, uncovering rare events (e.g. H3N2), potential undiagnosed asymptomatic cases (e.g. H1N1pdm), and co-circulating viruses, which may lead to genomic reassortments and the emergence of new reassortant viruses.